2003
DOI: 10.1002/bem.10123
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of human brain tissue measured less than 10 h postmortem at frequencies from 800 to 2450 MHz

Abstract: The dielectric properties of gray matter in the frequency range of 800-2450 MHz were measured on 20 human brains immediately after excision, less than 10 h after death. The brains were obtained during autopsy of 10 male and 10 female humans who died at ages between 47.5 and 87.5 years [70.4 +/- 9.8 years, mean +/- standard deviation (SD)]. The tissue temperature at the measurement sites ranged between 18 and 25 degrees C (21.35 +/- 1.6 degrees C, mean +/- SD). On each brain, four specific locations on the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 13 publications
0
60
1
1
Order By: Relevance
“…A number of studies of the dielectric properties of different human tissue have been made, [20]- [23] and there is a clear indication of a significant contrast between blood and white and gray brain matter. Originating in our own work with microwave tomography applied to breast cancer detection, [24], we have developed a helmet with microwave patch antennas, signal processing methods based on a machine learning algorithm and have performed numerical and phantom studies of hemorrhagic stroke detection, [25], [26], with encouraging results.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies of the dielectric properties of different human tissue have been made, [20]- [23] and there is a clear indication of a significant contrast between blood and white and gray brain matter. Originating in our own work with microwave tomography applied to breast cancer detection, [24], we have developed a helmet with microwave patch antennas, signal processing methods based on a machine learning algorithm and have performed numerical and phantom studies of hemorrhagic stroke detection, [25], [26], with encouraging results.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical phantom has relative permittivity of 78 in the inner layer and =53.53 in the outside layer. The relative permittivity of the physical phantom were 78.63 and 51.72 for inner and outer layer, respectively [10].…”
Section: Phantom Parameterizationmentioning
confidence: 99%
“…A further study of dielectric spectroscopy of canine myocardium during acute ischaemic stroke using the frequency band from 100 KHz to 6 GHz demonstrated the ability to detect ischaemic from non-ischaemic tissues [85]. In 2003, Schmid et al [86] studied the dielectric properties of brain tissues from 10 male and 10 female humans measured less than 10 hours after death. The results showed that the electrical conductivity of the grey matter was higher than in the results based on animal brain samples and excised samples of human brain tissues measured more than 24 hours post-mortem [86].…”
Section: Dielectric Properties Of Human Tissues At Microwave Frequenciesmentioning
confidence: 99%
“…In 2003, Schmid et al [86] studied the dielectric properties of brain tissues from 10 male and 10 female humans measured less than 10 hours after death. The results showed that the electrical conductivity of the grey matter was higher than in the results based on animal brain samples and excised samples of human brain tissues measured more than 24 hours post-mortem [86].…”
Section: Dielectric Properties Of Human Tissues At Microwave Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation